Irreversible investments, dynamic inconsistency and policy convergence - Rune Jansen Hagen; Gaute Torsvik (Center for Economic Studies and ifo Institute (CESifo), 2007)
We study a model where two parties, one from the left and one from the right, compete for position. The election is to be held in the near future and the outcome is uncertain. Prior to the election, the members of both parties nominate their prime ministerial candidates. Investors care about the outcome since they may invest in irreversible domestic production capital. We find that there is political convergence in the nomination process. In some circumstances, it is only the median voter of the left-wing party that elects a more moderate candidate. In other instances, the members of both parties nominate more conservative candidates, but there is still convergence. We also show that a higher probability of the left winning the election increases the degree of convergence, while a more globalised economy (greater capital mobility) reduces it.
Keywords: E61; F21; H24; P16; 330; Wahlverhalten; Investition; Politische Partei; Politisches Ziel